Biogenic scale up synthesis of ZnO nano-flowers with superior nano-photocatalytic performance. Issue 8 (2nd August 2020) - Din, Muhammad Imran; Najeeb, Jawayria; Hussain, Zaib; Khalid, Rida; Ahmad, Ghazia
Abstract: A novel green approach was adopted for carrying out the large scale synthesis of the Zinc oxide nanoflowers (ZNFs). The reducing power of maltose was utilized for reducing the precursor metal salt into NFs. The selection of the reaction constituents including water, and maltose as solvent, was done purely for achieving the goal of green synthesis. Capping agent of maltose was preferred over other biological stabilizers owing to its high solubility in water which removes all the problems found associated with the usage of the organic solvents. Similarly, usage of maltose as a reductant is not only beneficial from the economic point of view because of its cheapness but it is also highly valuable as it is an environmental friendly compound. Henceforth, an easy, simple, novel, facile and green method has been proposed for the synthesis of ZNFs. Engineered system exhibited excellent photocatalytic potential for the 2-nitrophenol (2-NP).